Saltwater Intrusion Effect on Water Supply Project in Sungai Semerak, Pasir Puteh, Kelantan, Malaysia - Samsudin, Mohamad Fikri; Aileen Tan Shau Hwai (JURNAL KESEHATAN LINGKUNGAN, 2025)
Introduction: In Kelantan, saltwater intrusion was a problem that worsened the water supply, especially groundwater, which was the main source of water supply. This study was conducted to study the suitability of Sungai Semerak as a site for constructing a water intake station in the Pasir Puteh District to provide an alternative water supply source that previously depended on groundwater. Methods: In this study, three approaches were taken to identify the suitable location. The approaches are the Water Quality Index (WQI) by Malaysia Environmental Department includes six water quality parameters of dissolved oxygen (DO), pH, chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS) and ammoniacal nitrogen (AN) with additional approach of Stratification of saltwater and Groundwater Quality. Result and Discussion: From the data gathered, the freshwater zone shows WQI was in Class III at 52.31, which is higher than 51.9, the lower limit of Class III , which is suitable for water supply with treatment and suitable for irrigation compared to the saline zone, WQI was 47.08, which is in Class IV. Groundwater quality of pH (5.95), Total Dissolve Solids (251.77 mg/L), Conductivity (416.2μS/cm), Turbidity (88.19 NTU), Calcium (14.54mg/L), Magnesium (6.25mg/L), Sodium (36.41mg/L), Bicarbonate (67.11mg/L), Chloride (26.03mg/L), Sulphate (4.67mg/L), Total Hardness (67.12mg/L) also shows acceptable readings for suitability for drinking water. Conclusion: Therefore, Sungai Semerak was suitable for building a water intake station as it was important in a developing state and country.